2001
DOI: 10.1007/s11664-001-0136-6
|View full text |Cite
|
Sign up to set email alerts
|

Surface tension measurements of the Bi-Sn and Sn-Bi-Ag liquid alloys

Abstract: The maximum bubble pressure method has been used to measure the surface tension of pure Bi, surface tension and density of liquid binary Bi-Sn alloys (X Bi = 0.2, 0.4, 0.6, and 0.8 molar fractions) at the temperature range from about 500 K to 1150 K. Similarly, there were investigated ternary alloys adding to the eutectic (3.8\at.%Ag-Sn) 0.03, 0.06, 0.09, and 0.12 molar fractions of Bi. The linear dependencies of densities and surface tensions on temperature were observed and they were described by straight-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 23 publications
5
30
1
1
Order By: Relevance
“…The works [12,13] cover the temperature range of the present measurements, whereas the alloy compositions are quite different. The Ag 3.46 Bi 9 Sn 87.54 alloy [10] has a composition very close to Ag 3.33 Bi 10 Sn 86.67 , one of the alloys investigated in the present study, and their values of the density and surface tension are comparable as well ( Table 2). Table 1 Surface tension and density together with the corresponding temperature coefficients of Sn-rich ternary liquid alloys of the Ag-Bi-Sn system [12] by up to 1.2 % ( Table 2).…”
Section: Surface Tension and Densitysupporting
confidence: 66%
See 1 more Smart Citation
“…The works [12,13] cover the temperature range of the present measurements, whereas the alloy compositions are quite different. The Ag 3.46 Bi 9 Sn 87.54 alloy [10] has a composition very close to Ag 3.33 Bi 10 Sn 86.67 , one of the alloys investigated in the present study, and their values of the density and surface tension are comparable as well ( Table 2). Table 1 Surface tension and density together with the corresponding temperature coefficients of Sn-rich ternary liquid alloys of the Ag-Bi-Sn system [12] by up to 1.2 % ( Table 2).…”
Section: Surface Tension and Densitysupporting
confidence: 66%
“…The density and surface tension experimental data for liquid Ag-Bi-Sn alloys have been reported elsewhere [10,12,13]. The works [12,13] cover the temperature range of the present measurements, whereas the alloy compositions are quite different.…”
Section: Surface Tension and Densitymentioning
confidence: 86%
“…It was also already shown that bismuth and silver can have a significant impact on the corrosion properties in case of Sn-based solder alloy in NaCl solutions [17,18]. Furthermore, the influence of bismuth addition on the microstructure and the properties of Sn-rich SnAg lead-free solders has been also widely studied [13,[19][20][21][22][23]. However, the effect of bismuth on the corrosion behaviour in the case of micro-alloyed solder alloy is not deeply addressed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier publications, [17][18][19][20][21], a qualitative agreement was observed between the experimental and the calculated surface tensions from Butler's model; however, the calculations have shown the increase of the surface tension vs. temperature (the positive temperature coefficient), the reasonable differences between the experimental and modelled data and also the curvilinear dependence of the surface tension vs. temperature (sometimes with the maximum) while from the experiment the straight line dependence vs. T with the negative value of temperature coefficient was observed. This was the main reason of the discussion of that problem conducted in [22] and [23].…”
Section: Surface Tension Modellingmentioning
confidence: 99%